Positive soil responses to different vegetation restoration measures in desert photovoltaic power stations - Meng, Ruibing; Meng, Zhongju; Jia, Ruiting; Li, Haonian; Cai, Jiale; Gao, Yue (Frontiers in Plant Science, 2025)
Scientific and reasonable vegetation restoration plays a pivotal role in enhancing soil quality, boosting ecosystem services, and ensuring the long-term stable operation of photovoltaic (PV) power stations in desert regions. To elucidate the response mechanisms of soil under different vegetation restoration implemented in PV power stations located in sandy areas, this study selected the PV power plant in Duguitala Township of the Hobq Desert as a representative research site. A systematic evaluation was conducted on the effects of four artificial vegetation restoration strategies, namely, Leymus chinensis (LC), Glycyrrhiza uralensis (GU), Artemisia ordosica (AO), and Hedysarum scoparium (HS) under panels and between panels. This analysis aimed to clarify the influence of different vegetation restoration approaches on soil quality in sandy regions and their underlying mechanisms. The findings revealed that these vegetation restoration measures significantly impacted soil texture, bulk density (BD), soil porosity (SP), soil water content, and water retention capacity. Specifically, LC and GU markedly improved soil physical structure and water retention capacities. Vegetation restoration substantially enhanced soil nutrient accumulation, with LC achieving the highest levels of multiple soil nutrient indices (total nitrogen (TN), total phosphorus (TP), and available potassium (AK)), HS exhibiting the highest level of available phosphorus (AP), and GU demonstrating superiority in total potassium (TK). These diverse vegetation restoration strategies exhibited potential advantages in improving soil fertility and promoting nutrient cycling at locations under PV panels. The soil quality index (SQI) showed that the effectiveness of the different vegetation measures in enhancing soil quality was ranked GU>LC>HS>AO>CK. This study not only provides robust theoretical support for ecological restoration in desert PV plants, but also offers practical experience applicable to vegetation restoration efforts in similar ecological environments, thereby possessing significant ecological and practical value.